Research on Drivers' Perception on the Maintenance of Air Filters for Internal Combustion Engines. (2016) - Toma, Marius; Bobâlcă, Claudia
Abstract: The previous research on air filters has shown that they are replaced prematurely before reaching full capacity of utilization, leading to increasing maintenance costs and to reduced engine protection against abrasive wear. Also, the customers play a very important part because beyond the warranty period, they have the last word, making decisions about replacing or not the air filters. In this context, the present research aims to analyze drivers' perceptions on the air filters maintenance for internal combustion engines. We also investigated drivers' level of knowledge about the consequences of their decisions regarding air filters maintenance. We conducted a quantitative research, using the survey method based on a questionnaire. Most respondents are aware of the main filters used by cars systems. The best known filter is the fuel filter and the less known is cabin air filter. The most important characteristic in selecting air filters is higher filtering efficiency. When choosing the air filter, the first criterion taken into account by respondents is the recommendations from the maintenance and repair handbook of the car. The main consequence of dust penetration inside the internal combustion engine is the engine's wear. This study is useful both for practitioners and academics.